Transparency Principle in Local Revenue Governance: An Administrative Law Perspective - Athaya Faiz Wijayanti; Muh. Ali Masnun; Andy Usmina Wijaya (NOVUM : JURNAL HUKUM, 2025)
This study offers an integrated normative empirical assessment of transparency implementation in local revenue governance, highlighting the structural gap between legal standards and administrative capacity. This study also analyzes the implementation of the principle of transparency in the management of Local Revenue (PAD) by the Regional Financial and Asset Management Agency (BPKAD) of Surabaya City as a manifestation of the application of the General Principles of Good Governance (AAUPB). Using a sociological legal empirical research method, this study combines primary data from interviews with the Head of the Treasury and Accounting Division of BPKAD Surabaya City with secondary data in the form of laws and regulations, official documents, and scientific literature. The results of the study show that BPKAD Surabaya City has implemented the principle of openness through proactive publication, an integrated information system, public information request services, and an SPBE-based data security mechanism. However, implementation still faces significant challenges, including normative aspects (interpretation of the boundaries between open and exempt information, legal timeframe inconsistencies), technical aspects (digital human resource limitations, system downtime, data integration), and institutional aspects (political pressure, information sensitivity, bureaucratic culture). This study concludes that although the regulatory framework is comprehensive, implementation of the principle of openness requires harmonization of legal norms with empirical capacity, strengthening of digital infrastructure, improvement of human resource competencies, and a sustained commitment to realizing transparent and accountable regional financial management.